Trends in the therapeutic use of the transplantations of hematopoietic stem cells - Jędrzejczak, Wiesław Wiktor (Przewodnik Lekarza/Guide for GPs, 2010)
Transplantation of hematopoietic cells (with exception of multiple myeloma) is performed with the goal to cure the disease that was the indication for the procedure. In multiple myeloma cure is not achieved but survival after transplantation is prolonged. Transplantation of hematopoietic cells is an umbrella term for a number of related procedures that undergo constant evolution. On one hand, new procedures are being introduced such as transplantation after non-myeloablative conditioning, intramedullary transplantation, transplantation of cord blood and on the other hand there is improvement in matching of unrelated donors and their number is steadily increasing. Attempts to use haploidentical donors are advanced. There is a constant evolution of indications for transplantation. While their number in chronic myelocytic leukemia has decreased, what is associated with introduction of effective thyrosine kinase inhibitors more frequently hematopoietic transplantation is performed for newer indications such as chronic lymphocytic leukemia and myelofibrosis. New indication is diabetes type I, where if transplantation is performed sufficiently early in the course of disease independence from exogenous insulin is achieved. While transplantation of hematopoietic cells is mature method it is still a method under development.